Numerical Simulations for Aerodynamic Performance of a Butterfly-Like Flapping Wing-Body Model with Various Wing Planforms (Communications in Computational Physics, 2020)
Wing planform is one of important factors for lift and thrust generation andenhancement in flapping flight. In this study, we numerically investigate the effect ofwing planform on aerodynamic performance of a butterfly-like flapping wing-bodymodel by using the immersed boundary-lattice Boltzmann method. The model flapsdownward for generating the lift force and backward for generating the thrust forcelike an actual butterfly. We calculate the aerodynamic performance such as the liftforce, the thrust force, the power expenditure, and the power loading for (i) trapezoidalwing planforms with various taper ratios (ratio of the wing-tip length to the wing-rootlength), (ii) rectangular wing planforms with various aspect ratios (ratio of the squareof the wing length to the wing area), and (iii) an actual butterfly's wing planform atthe Reynolds number of 500. As a result for the trapezoidal and rectangular wingplanforms, we find that the lift and thrust forces increase at the cost of the powerexpenditure as the taper ratio increases and as the aspect ratio increases. In addition,it is found that the actual butterfly's wing planform is more efficient than any of thetrapezoidal and rectangular wing planforms.
Keywords: Lattice Boltzmann method; immersed boundary method; flapping flight; aerodynamic performance; wing planform.